THE USE OF HEMOSTATIC AGENT "HEMOBEN" DURING SURGICAL NECRECTOMY OPERATIONS - Yunusov Oybek Turaevich; Yunusova Guzal Faizullaevna (Scholar Express Journals, 2025)
In modern surgical practice there is a need for systematization of data on the effectiveness of “Hemoben” application, determination of optimal indications for its use, development of standardized approaches to the use of the drug in various types of necrectomy. This determines the relevance and practical significance of research in this direction.
Keywords: hemostasis; burns; necroectomy